ASESMEN KOMPETENSI MINIMUM SEBAGAI ALTERNATIF PENINGKATAN KEMAMPUAN LITERASI BACA TULIS SISWA SEKOLAH DASAR - Priska Nurlia Br Simanungkalit; Novi Astika Rambe; Korinti Nalsalisa Br Milala; Dessy Haqiki Wulandari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Problems in the national exam arise at various stages, starting from pre-implementation, during implementation, to post-implementation. The use of national exam results as an assessment of student success in the learning process is not appropriate. Thus, the evaluation system in Indonesia has changed with the abolition of the national exam. The impact on the learning process in schools, instead, is the Minimum Competency Assessment (MCA) and character survey. This study aims to explain the concept of Minimum Competency Assessment (MCA) as an effort to improve students' literacy skills in primary schools. The method used is a literature study. The results explain that AKM does not refer to mastery of curriculum-aligned material as in the national exam, but is designed to map and improve the overall quality of education. AKM focuses on measuring literacy competencies. Thus, it is expected that the implementation of AKM can improve students' literacy skills in primary schools.